Effect of excavation blasting vibration on adjacent buried gas pipeline in a metro tunnel. (November 2018) - Jiang, Nan; Gao, Tan; Zhou, Chuanbo; Luo, Xuedong
Abstract: To ensure the safety of gas pipeline during tunnel blasting excavation, it is crucial to investigate the dynamic response of gas pipeline to blast vibration under tunnel excavation. In this paper, the blasting excavation of Beijing metro line 16 was selected as a case, and the blasting vibrations in the field were monitored. Based on the field monitoring data, a mathematical model was established and proposed to describe the attenuation of peak particle velocity (PPV) of ground surface soils with respect to the depth of tunnel blasting. Next, a 3D numerical model was established to analyze the response characteristics of burial gas pipeline subjected to blasting vibration and its reliability was verified using the field monitoring data. The effects of metro tunnel blasting vibration on gas pipeline under different tunnel blasting conditions were further calculated, and the dynamic response characteristics of soil, pipe and pipe surrounding soil were discussed. At last, to better and more conveniently assess and predict the influence of blasting vibration, a PPV prediction model of gas pipeline under metro tunnel excavation blasting for this project was proposed.